Controllable low-strength filling material based on engineering waste soil and preparation method and application thereof
Patent Information
- Application Number
- CN202611115871.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-27
AI Technical Summary
因此,工程渣土资源化利用产品面临性能不稳定、利用成本高、应用场景和规模受限等瓶颈,亟需发展面向工程弃渣土的就地化、规模化与高效化利用技术
[0044](1)本发明适用于利用各种类型工程渣土、淤泥等工程固废,且最大程度利用工程固废和工业固废开发了可替代传统水泥混凝土回填材料,不仅利废低碳环保,成本低,而且实现多源固废的高效协同利用,应用前景广阔。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of engineering waste soil resource utilization technology, and in particular to a controllable low-strength backfill material based on engineering waste soil, its preparation method and application. Background Technology
[0003] The market demand for backfill materials, roadbed materials, and ecological restoration soil in the engineering construction sector continues to rise. The constraints on the extraction and utilization of natural sand and gravel and high-quality soil resources are constantly strengthening. These supply and demand demands are jointly driving the transformation of construction waste from "waste awaiting disposal" into a recyclable green resource. Its resource utilization has become an inevitable direction for balancing engineering construction needs and alleviating environmental pressure. At the same time, construction waste comes from a wide range of sources and often contains impurities such as crushed stone and construction debris. Its particle size distribution and mineral composition are complex and variable, with large fluctuations in composition and significant differences in moisture content. In particular, silt-type construction waste generally has a high organic matter content, and components such as humic acid coat soil particles, inhibiting the hydration reaction of stabilizing and solidifying materials. This leads to slow setting and hardening, large dispersion in solidification strength, and poor uniformity, significantly increasing the technical difficulty of stabilizing and preparing resource-based products. Therefore, resource-based utilization products of construction waste face bottlenecks such as unstable performance, high utilization costs, and limited application scenarios and scale. There is an urgent need to develop on-site, large-scale, and efficient utilization technologies for construction waste.
[0004] Against this backdrop, Controlled Low-Strength Material (CLSM), with its advantages of good fluidity, self-compacting properties, adjustable strength, and availability of locally sourced materials, offers a new technological path for the efficient disposal and resource utilization of engineering waste. This type of material, based on engineering waste and combined with a small amount of cementitious materials and water, can be formulated into a fluid backfill material that meets the requirements of backfilling projects. It can not only dispose of large quantities of engineering waste but also replace traditional sand and gravel fillers in engineering scenarios such as foundation pit backfilling, trench backfilling, and road base courses, achieving resource recycling through "waste replacing stone." However, given the high variability in the properties of engineering waste, establishing mix design methods and construction quality control systems that match the characteristics of different sources and types of waste is crucial for its controllable, stable, and large-scale utilization. This is also the core scientific issue in developing controlled low-strength backfill materials based on engineering waste. Summary of the Invention
[0005] In view of this, embodiments of the present invention provide a controllable low-strength backfill material based on engineering waste soil. This material efficiently utilizes waste soil and industrial solid waste to synergistically regenerate low-carbon engineering materials, making use of waste and protecting the environment, with low cost and high cost-effectiveness.
[0006] The present invention also provides a method for preparing the above-mentioned materials.
[0007] The embodiments of the present invention also provide applications of the above-mentioned materials.
[0008] According to one aspect of the present invention, a controllable low-strength backfill material based on engineering waste soil is provided, comprising the following raw materials in parts by weight: 80-95 parts of engineering waste soil, 5-15 parts of waste soil solidification agent, 0.1-10 parts of anti-organic matter regulating material, 0.1-2 parts of mud plasticizer, 0-5 parts of hardening regulator and 0-2 parts of density regulator;
[0009] The raw materials meet the following conditions:
[0010] (i) The anti-organic matter regulation material comprises at least two of the following: mixed polyol amines, zirconium acetate, and ultrafine metakaolin;
[0011] (ii) The slurry plasticizer comprises at least two of the following: acrylic acid-acrylamide modified naphthalene sulfonate copolymer, polyaspartic acid, layered silica, and cyclic sodium polyphosphate;
[0012] (iii) The slag solidification agent comprises the following components: high-alumina ferrophase cementitious material, spodumene smelting slag powder, converter steel slag powder, high-activity slag powder, circulating fluidized bed fly ash and gypsum powder; wherein, the components have the following characteristics: (1) High-alumina ferrophase cementitious material: C4AF > 15wt%; calcium aluminate (CA) content > 50wt%; specific surface area 350-400m² 2 / kg; (2) Lithium spodumene smelting slag powder: SiO2 content + Al2O3 content > 70wt%, amorphous glass phase > 40wt%, D 50 <10μm; (3) Converter steel slag powder: CaO content between 50wt% and 60wt%, CaO to SiO2 mass ratio >2.5, (FeO+Fe2O3) <20wt%, f-CaO content <2wt%, D 50 <10μm, specific surface area >500m² 2 / kg; (4) High-activity slag powder: the ratio of the sum of the masses of CaO, MgO, and Al2O3 to the sum of the masses of SiO2, Ti2O, and MnO is >1.6, the amorphous glass phase is >90wt%, the MgO content is <8wt%, the Fe2O3 content is <2.5wt%, and the D 50 <10μm, specific surface area >500m² 2 / kg; (5) Circulating fluidized bed fly ash: CaO content between 10-20wt%, D 50 <10μm; (6) Gypsum powder: The components include β-type desulfurized gypsum powder or β-type phosphogypsum powder, β-CaSO4·1 / 2H2O content ≥80wt%, 80μm sieve residue ≤10wt%.
[0013] According to some embodiments of the present invention, the controllable low-strength filling material comprises the following raw materials in parts by weight: 80-95 parts of engineering waste soil, 5-15 parts of waste soil solidification agent, 0.1-10 parts of anti-organic matter regulating material, 0.1-2 parts of mud plasticizer, 0-5 parts of hardening regulator and 0-2 parts of density regulator.
[0014] According to some embodiments of the present invention, the anti-organic matter regulation material comprises at least two of a mixture of polyol amines, zirconium acetate, and ultrafine metakaolin.
[0015] According to some embodiments of the present invention, the anti-organic matter regulation material comprises a mixed polyol amine, zirconium acetate and ultrafine metakaolin, wherein the mass ratio of the mixed polyol amine, zirconium acetate and ultrafine metakaolin is 1:3~5:10~20.
[0016] According to some embodiments of the present invention, the mixed polyamine comprises 15-25 parts of N-methyldiethanolamine, 20-40 parts of triethanolamine, 15-25 parts of diisopropanolamine, and 20-40 parts of triisopropanol.
[0017] According to some embodiments of the present invention, the particle size of the ultrafine metakaolin is above 3000 mesh.
[0018] According to some embodiments of the present invention, the slurry plasticizer contains an acrylic acid / acrylamide modified naphthalene sulfonate copolymer. The acrylic acid / acrylamide modified naphthalene sulfonate copolymer is mainly obtained by modifying a traditional naphthalene-based water-reducing agent. It is an anionic hybrid polymer formed by introducing hydrophilic / functional side chains of acrylic acid (providing carboxyl groups –COOH) and acrylamide (providing amide groups –CONH2) through free radical copolymerization, using a traditional naphthalene sulfonic acid-methylene bridge-sulfonic acid group in the polymer. The naphthalene ring – methylene bridge – sulfonic acid group in the polymer provides strong electrostatic repulsion; -CH2-CH(COO-) enhances dispersion and chelation ability; -CH2-CH(CONH2) improves slump retention and molecular chain flexibility, synergistically achieving a dual dispersion mechanism of "electrostatic repulsion + steric hindrance". The filling material of this invention is prepared from a large amount of slag soil. Conventional water-reducing agents and other admixtures are ineffective due to adsorption by the layered structure of the slag soil. This invention uses a specific modified acrylic acid / acrylamide-modified naphthalene sulfonate copolymer as an admixture. Through electrostatic repulsion and steric hindrance, as well as the synergistic effects of reducing flocculation caused by ion bridging and weakening interlayer van der Waals forces, it can effectively overcome the particle agglomeration phenomenon in slag soil-based fluidized solidified soil, release free water and disperse soil particles, and form a high fluidized solidified soil filling material with low water consumption and self-compacting properties.
[0019] According to some embodiments of the present invention, the preparation method of the acrylic acid / acrylamide modified naphthalene sulfonate copolymer includes the following steps:
[0020] Acrylic acid is neutralized to a degree of neutralization of 65-75%, and mixed with acrylamide in a molar ratio of 1:0.9-1.1 to prepare an aqueous solution (preferably, a complexing agent is added to remove impurities) to obtain an acrylic acid-acrylamide monomer solution;
[0021] The acrylic acid-acrylamide monomer solution is added to a β-naphthalenesulfonate solution (preferably, the molar ratio of naphthalenesulfonate, acrylic acid, and acrylamide is 1:0.9~1.1:0.9~1.1) to remove oxygen. An initiator (preferably a mixture of sodium persulfate and sodium bisulfite, with the amount of initiator added preferably being 5~7% of the total mass of the monomer) and a chain transfer agent (preferably mercaptopropionic acid) are added. The reaction is carried out under heating, and the pH of the system after the reaction is controlled to be 7~8 to obtain the final product.
[0022] According to some embodiments of the present invention, the slurry plasticizer is composed of an acrylic acid / acrylamide modified naphthalene sulfonate copolymer and polyaspartic acid in a mass ratio of 8 to 10:1.
[0023] According to some embodiments of the present invention, the mass ratio of the curing agent to the pretreated waste soil is 1:7~10.
[0024] According to some embodiments of the present invention, the mass ratio of the curing agent to the pretreated waste soil is 8~12:80~95.
[0025] According to some embodiments of the present invention, the mass ratio of the curing agent to the pretreated waste soil is 1:7.5~9.
[0026] According to some embodiments of the present invention, the mass ratio of the curing agent to the pretreated waste soil is 1:8~9.
[0027] According to some embodiments of the present invention, the hardening regulator comprises refining slag powder from an air-quenched LF furnace.
[0028] According to some embodiments of the present invention, the amorphous C in the refining slag powder of the LF furnace quenching is... 12 A7 mineral phase content >30wt%, β-C2S content >20wt%.
[0029] According to some embodiments of the present invention, the slag solidifying agent includes high-alumina iron-phase cementing materials, spodumene smelting slag powder, converter steel slag powder, highly active slag powder, circulating fluidized bed fly ash, and gypsum powder.
[0030] According to some embodiments of the present invention, the slag solidification agent is composed of the following parts by weight: 5-15 parts of high-alumina ferrophase cementitious material, 5-15 parts of spodumene smelting slag powder, 20-40 parts of converter steel slag powder, 20-40 parts of highly active slag powder, 10-30 parts of circulating fluidized bed fly ash, and 5-15 parts of gypsum powder. The solidification agent of the present invention has good acid resistance, and the product system has been changed. Traditional solidification agents have poor acid resistance, and a large amount of calcium hydroxide is easily neutralized and decomposed by organic matter, leading to easy failure.
[0031] According to some embodiments of the present invention, the density regulator includes polyethyleneimine, rosin soap, and modified α-alkenyl sulfonate sodium.
[0032] According to some embodiments of the present invention, the mass ratio of the polyethyleneimine, rosin soap and modified α-olefin sulfonate sodium is 1~2:4~6:3~5.
[0033] According to some embodiments of the present invention, the particle size of the engineering waste soil is less than 5 mm.
[0034] According to another aspect of the present invention, a method for preparing the above-mentioned controllable low-strength filling material is provided, comprising the following steps:
[0035] The waste soil from the project is mixed with water and then stirred and ball-milled. During the stirring and ball-milling process, an anti-organic matter regulating material is added to form a slurry. A waste soil solidifier and a slurry plasticizer are then added to the slurry to obtain the final product.
[0036] According to some embodiments of the present invention, the particle size D of the mud is... 50 It is 150-250μm.
[0037] According to some embodiments of the present invention, the engineering waste soil is engineering waste soil with a particle size of less than 5 mm. It can be initially crushed to a size of less than 5 mm by a crusher, and then mixed and stirred in appropriate volumes to achieve homogenization of the waste soil.
[0038] According to another aspect of the present invention, a method for using the above-mentioned controllable low-strength filling material is provided, comprising the following steps:
[0039] Before pouring, a hardening regulator and / or density regulator are added to the controllable low-strength filling material, and the mixture is then poured.
[0040] Hardening regulators and / or bulk density regulators may be added as needed.
[0041] According to another aspect of the present invention, the application of the above-mentioned controllable low-strength filling material in the construction of infrastructure, transportation engineering or mining engineering is provided.
[0042] According to some embodiments of the present invention, the infrastructure includes at least one of the following: backfilling of sump trenches, backfilling of pipe corridors, backfilling of foundation pits, filling of karst caves, filling of mines, foundation treatment, roadbed and pavement.
[0043] The present invention has at least the following beneficial effects:
[0044] (1) This invention is applicable to the use of various types of engineering waste such as slag and silt, and has developed a material that can replace traditional cement concrete backfill material by making the maximum use of engineering waste and industrial waste. It is not only waste-utilizing, low-carbon and environmentally friendly, and low-cost, but also realizes the efficient synergistic utilization of multi-source solid waste, with broad application prospects.
[0045] (2) This invention can achieve precise control and comprehensive performance optimization of the fluidized solidified soil filling material prepared from engineering waste soil through the synergistic effect of anti-organic matter regulating materials, mud plasticizers, hardening regulators, and volume regulating materials. It effectively overcomes a series of prominent problems caused by engineering waste soil of different types / sources and complex composition, such as the inability to meet the requirements of the prepared fluidized solidified soil filling material, unstable performance, and poor adaptability to application scenarios.
[0046] (3) The slag solidification agent developed and utilized in this invention is based on the coordinated hydration effect of various aluminosilicate waste residues, forming a new low-carbon solidification material with superimposed hydration effect and excellent early and late hardening performance. It can not only replace traditional high-energy-consuming cement solidification agents, but also overcome the poor solidification effect of cement and traditional solidification agents on slag with high organic matter content, achieving excellent solidification performance. Specifically, in the slag solidification agent components of this invention, the high-alumina iron phase cementitious material first hydrates to generate a large amount of ettringite and hydrated calcium aluminoferrite, rapidly constructing the early skeleton. The Ca produced by the dissolution of high-alkalinity (CaO / SiO2>2.5) converter steel slag 2+ The alkaline environment provides nuclei and alkalinity for the early hydration of spodumene smelting slag and highly active slag powder, promoting glass dissociation and the release of active silica-alumina components, further generating C-(A)-SH gel to fill the pores. The porous structure of circulating fluidized bed fly ash can adsorb free water and harmful impurities in the sludge, while gypsum powder provides sulfate ions for the formation of ettringite, promoting the continuous hydration reaction. Under the synergistic effect of multiple components, a product system of C-(A)-SH, AFt (ettringite), and Ca(OH)2 is formed (breaking the traditional silicate cement product system dominated by CSH gel and Ca(OH)2, which is beneficial for solidification environments of complex waste soil such as acid and salt erosion resistance). The hydration products intertwine to form a dense spatial network, firmly binding the sludge particles, significantly reducing the soil porosity, realizing the conversion of free water to chemically bound water, significantly improving the strength and impermeability of silty soil, avoiding the leakage of harmful components, and achieving a stable solidification effect.
[0047] (4) This invention addresses the characteristics of different slag minerals and layered structures by using a novel mud plasticizer based on two or more combinations of acrylic acid-acrylamide modified naphthalene sulfonate copolymer, polyaspartic acid, layered silica, and cyclic sodium polyphosphate. This effectively overcomes the adsorption, flocculation, and agglomeration of particles in slag-based fluidized solidified soil, allowing free water to be released and soil particles to disperse, forming a high-fluidity solidified soil backfill material with low water consumption and self-compacting properties. Specifically, ① the acrylic acid / acrylamide modified naphthalene sulfonate copolymer adsorbs onto the surface of soil particles through sulfonic acid groups, forming a double-layer structure that generates electrostatic repulsion. Simultaneously, the acrylamide side chains provide steric hindrance, preventing particle re-agglomeration; ② the carboxyl and amide groups of polyaspartic acid can repel metal ions (such as Ca2+) in the slag soil. 2+ Mg 2+ ) Forming complexes, reducing flocculation caused by ion bridging, while its hydrophilic groups enhance the thickness of the hydration layer on the particle surface; ③ Layered silica, with its layered structure, can weaken the interlayer van der Waals forces, thereby dispersing clay particles. When used in combination with polyaspartic acid, the lamellar structure of layered silica can form a physical barrier, delaying particle sedimentation; ④ Cyclic sodium polyphosphate, whose phosphate ions complex with high-valence metal ions (such as Fe) in clay minerals. 3+ Al 3+ This process disrupts interparticle ionic bonds and inhibits the deactivation of dispersants by metal ions. Furthermore, the combination of acrylic copolymer and polyaspartic acid simultaneously exerts electrostatic repulsion and chelation effects, significantly improving dispersion efficiency. The combination of cyclic sodium polyphosphate and layered silica further reduces thixotropy of the slurry, making it suitable for low-water-consumption, high-fluidity solidified soil backfill material systems.
[0048] (5) In response to the severe impact of organic humic acid (especially fulvic acid and humic acid) in slag soil on the solidification performance of slag soil, the organic matter-regulating material of this invention can effectively solve the influence of humic acid in silty slag soil on the performance of backfill materials. The mixed polyol amine, zirconium acetate, and ultrafine metakaolin in the organic matter-regulating material have excellent synergistic effects. Among them, the Zr in zirconium acetate 4+ Strong coordination ability deprives fulvic acid from complexing Ca² in organic matter. + The activity (breaking the "complex") releases Ca² + CH3COO - The organic groups released during decomposition compete with fulvic acid for adsorption sites (breaking the "adsorption" barrier), and the dispersion effect disrupts the continuity of the fulvic acid film (breaking the "film formation" barrier), thus forming an excellent resistance to organic matter; the ion complexation and competitive shielding mechanism of the mixed polyol amine preferentially binds to Ca²⁺ in the liquid phase. + / Al³ + Formation of stable, soluble complexes, which both promotes hydration and reduces the impact of fulvic acid on Ca²⁺. + and Al³ +The predatory binding of ions maintains the stability of the hydration product framework; the competitive adsorption and film-forming blocking effect of ultrafine metakaolinite, with its porous structure and high specific surface area, preferentially adsorbs free fulvic acid molecules in the system, reducing the adsorption load on the surface of cementitious minerals and preventing the formation of dense hydrophobic films. These individual components, through coordination, complexation, or adsorption, can resist the adverse effects of organic matter from different dimensions. The synergistic effect of these three components—zirconium acetate breaking the complex and releasing ions, mixed polyol amines stabilizing ions and promoting hydration, and ultrafine metakaolinite inhibiting film formation—together forms a complete anti-organic matter system, far superior to the effect of a single component.
[0049] (6) This invention addresses the issue that the hardening time of fluidized solidified soil in different scenarios is long and cannot meet the needs of some rapid construction hardening processes, by modifying soil rich in C 12 A7 and dicalcium silicate quenched LF furnace refined slag powder are used as hardening regulators. On the one hand, they promote the solidification and hardening of the soil after the slag solidifier is impregnated. On the other hand, their rapid hydration combines with the surrounding soil particles and consumes water, promoting the formation of the hardened skeleton, thereby promoting the hardening rate of the slag-based fluidized solidified soil filling material.
[0050] (7) The present invention utilizes a combination of polyethyleneimine with sodium rosinate and modified sodium α-olefin sulfonate to form a density regulator suitable for different slag-based fluidized solidified soil filling materials. Polyethyleneimine can play a role in stabilizing foam. By introducing micro-nano bubbles that do not affect the mechanical properties, the volume of fluidized solidified soil can be controlled and adjusted to meet the application requirements of fluidized solidified soil filling materials with different volume densities.
[0051] (8) The controllable filling material of the present invention has an advanced process flow from slag pretreatment → slurry preparation → fluidized soil preparation → hardening time adjustment → volume density adjustment. It not only overcomes the problems of performance fluctuation of traditional fluidized solidified soil due to different types of slag and its adaptability to difficult-to-handle slag (such as: large sandy slag, viscous silt, etc.), but also ensures the homogenization, standardization and adjustability of the slurry through the slurry preparation-storage process, which is conducive to industrial-scale production and quality assurance. At the same time, the adjustment of different properties such as hardening time and volume density maximizes the performance diversity of the product, which can meet the needs of different scenarios and construction requirements, and greatly improves its promotion and adaptability. Detailed Implementation
[0052] The following will clearly and completely describe the concept and technical effects of the present invention in conjunction with embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention. Unless otherwise specified, the experimental methods used in the embodiments are conventional methods; the materials and reagents used, unless otherwise specified, are commercially available. Unless otherwise specified, the same parameter value is the same in all embodiments. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0053] In the description of this invention, references to terms such as "some embodiments" indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0054] Unless otherwise specified, "wt%" in this invention represents a percentage by mass. "Parts" represents the number of parts by mass.
[0055] In response to a series of problems such as the huge volume of engineering waste soil, complex and fluctuating composition, large particle size differences, and serious impact of organic matter, resulting in low resource utilization rate and bottlenecks such as extensive and low-value utilization methods, this invention provides a controllable low-strength backfill material based on engineering waste soil. It efficiently utilizes waste soil and industrial solid waste to co-generate low-carbon engineering materials, which is environmentally friendly, low-cost, and cost-effective.
[0056] This invention addresses the issue of co-processing engineering waste soil from multiple sources of industrial solid waste. Based on the pretreatment of engineering waste soil, it utilizes low-carbon, high-performance solidifying agents, slurry plasticizers, and regulators derived from industrial solid waste. Through specific processing techniques, a controllable, low-strength backfill material based on engineering waste soil is prepared. This material can be used in various infrastructure, transportation, and mining projects, enabling large-scale, efficient utilization of engineering waste soil and industrial solid waste. It achieves synergistic and efficient utilization of multiple solid waste sources, promoting waste recycling and environmental protection, while offering low cost and broad application prospects. The preparation method of this invention transforms the resource utilization of engineering waste soil towards refinement and high value. Furthermore, the preparation process is simple to operate, has a wide range of applications, is particularly suitable for large-scale industrial production, and the resulting material has broad application areas.
[0057] According to some embodiments of the present invention, the controllable low-strength backfill material based on engineering waste soil comprises the following raw materials in parts by weight: 80-95 parts engineering waste soil, 5-15 parts waste soil solidification agent, 0.1-10 parts organic matter control material, 0.1-2 parts mud plasticizer, 0-5 parts hardening regulator, 0-2 parts density regulator, and 50-150 parts water. The organic matter control material is a combination of mixed polyol amines, zirconium acetate, calcium acetate, and ultrafine metakaolin.
[0058] The slag solidification agent is composed of the following components in parts by weight: 5-15 parts high-alumina ferrophase cementitious material, 5-15 parts spodumene smelting slag powder, 20-40 parts converter steel slag powder, 20-40 parts high-activity slag powder, 10-30 parts circulating fluidized bed fly ash, and 5-15 parts gypsum powder. The components must satisfy the following conditions:
[0059] (1) High-alumina iron phase cementitious materials: C4AF > 15wt%; calcium aluminate (CA) content > 50wt%; specific surface area 350-400m² 2 / kg;
[0060] (2) Spodumene smelting slag powder: (SiO2+Al2O3)>70wt%, amorphous glass phase>40wt%, D 50 <10μm;
[0061] (3) Converter slag powder: CaO content between 50wt% and 60wt%, CaO to SiO2 mass ratio > 2.5, (FeO + Fe2O3) < 20wt%, f-CaO content < 2wt%, D 50 <10μm, specific surface area >500m² 2 / kg;
[0062] (4) High-activity slag powder: (CaO+MgO+Al2O3) / (SiO2+Ti2O+MnO)>1.6 (mass ratio), amorphous glass phase>90wt%, MgO content<8wt%, Fe2O3 content<2.5wt%, D 50 <10μm, specific surface area >500m² 2 / kg;
[0063] (5) Circulating fluidized bed fly ash: CaO content 10-20wt%, D 50 <10μm;
[0064] (6) Gypsum powder: The components include β-type desulfurized gypsum powder or β-type phosphogypsum powder, with β-CaSO4·1 / 2H2O content ≥80wt% and 80μm sieve residue ≤10wt%.
[0065] The slurry plasticizer is two or more of the following: acrylic acid-acrylamide modified naphthalene sulfonate copolymer, polyaspartic acid, layered silica, and cyclic sodium polyphosphate.
[0066] The hardening regulator is LF furnace refining slag powder (of which amorphous C) 12 A7 mineral phase content >30wt%, β-C2S content >20wt%.
[0067] The density regulator is a combination of polyethyleneimine, rosin soap, and modified α-alkenyl sulfonate sodium.
[0068] The method for preparing the controllable low-strength backfill material based on engineering waste soil includes the following steps:
[0069] (1) Pretreatment of engineering waste soil: First, the engineering waste soil is initially crushed to a size of less than 5mm by a crusher, and then mixed and stirred in batches of appropriate volume to achieve homogenization of the waste soil;
[0070] (2) Engineering waste soil slurry preparation: The pretreated waste soil and water are mixed and ground in an overflow wet ball mill according to the corresponding proportion. During this process, anti-organic matter control materials are added to reduce or solve the negative impact of organic matter in the waste soil on performance, forming a slurry with a particle size D50 of 150-250μm and uniform texture. The prepared homogeneous slurry can also be transported through pipeline to a long-term storage tank for subsequent preparation of fluidized solidified soil filling material.
[0071] (3) Preparation of fluidized solidified soil filling material: The prepared homogeneous slurry is put into a mixing tank, and then the slag solidifying agent and slurry plasticizer are added in the corresponding proportions and stirred evenly to form fluidized solidified soil filling material for shipment.
[0072] The method of using the controllable low-strength backfill material based on engineering waste soil is as follows:
[0073] The aforementioned materials are transported to the application site and poured on-site as needed. The controllable low-strength filling material can be used for backfilling of trenches, pipe corridors, foundation pits, karst caves, mines, foundation treatment, roadbeds, pavements, and other infrastructure, transportation, and mining projects. It can also replace traditional shotcrete materials for ditch slope protection, river reinforcement, and mountain stabilization projects, solving the problem of difficult traditional compaction.
[0074] Before on-site application and pouring, a hardening regulator can be added to the transport mixer truck or on-site fluidized soil mixing tank to adjust the hardening time of the fluidized solidified soil filling material, thereby meeting the different hardening time requirements of on-site construction; at the same time, before on-site application and pouring, a density regulator can also be added to the on-site fluidized soil mixing tank to adjust the density and volume of the fluidized solidified soil filling material, thereby meeting the different volumetric density requirements during application.
[0075] The proportions of each raw material in the following examples and control group are all by mass parts, and the raw materials used are described below:
[0076] Construction waste A is clayey waste soil with a humic acid content of no more than 0.2 wt%, while construction waste B is high-organic silty waste soil with a humic acid content of 5 wt%.
[0077] Curing agent used ① It is prepared by mixing 10 parts of high-alumina iron-phase cementitious material, 10 parts of spodumene smelting slag powder, 30 parts of converter steel slag powder, 30 parts of highly active slag powder, 20 parts of circulating fluidized bed fly ash, and 10 parts of gypsum powder; curing agent ② High-alumina iron-phase cementitious material; curing agent ③ It is prepared by mixing 30 parts of converter steel slag powder and 70 parts of highly active slag powder; curing agent ④ It is prepared by mixing 10 parts of spodumene smelting slag powder, 30 parts of converter steel slag powder, and 10 parts of gypsum powder; curing agent ⑤ It is prepared by mixing 10 parts of spodumene smelting slag powder, 30 parts of converter steel slag powder, 30 parts of highly active slag powder, and 20 parts of circulating fluidized bed fly ash.
[0078] The organic matter regulation material used ① Composed of 5 parts mixed polyol amines, 20 parts zirconium acetate, and 75 parts ultrafine metakaolin; an organic matter-regulating material. ② Composed of 5 parts mixed polyol amines and 75 parts ultrafine metakaolin; an organic matter-regulating material. ③ Composed of 20 parts zirconium acetate and 75 parts ultrafine metakaolin; an organic matter-regulating material. ④ It is composed of 5 parts of mixed polyol amines and 20 parts of zirconium acetate.
[0079] The slurry plasticizer used is composed of 90 parts acrylic acid / acrylamide modified naphthalene sulfonate copolymer and 10 parts polyaspartic acid. The source information of its raw materials is as follows:
[0080] (1) The preparation method of acrylic acid / acrylamide modified naphthalene sulfonate copolymer is as follows: The preparation method of acrylic acid / acrylamide modified naphthalene sulfonate copolymer is as follows: Prepare a β-naphthalene sulfonate mother liquor with a solid content of 35% (produced by Shandong Wanshan Chemical Co., Ltd.) for later use; neutralize acrylic acid with 30% NaOH to a neutralization degree of 70%, and mix it with acrylamide at a molar ratio of 1:1 to prepare an aqueous solution with a total monomer mass fraction of 25%, and add 0.1% disodium ethylenediaminetetraacetate to complex impurities. Finally, add the acrylic acid-acrylamide monomer solution to the naphthalene sulfonate solution (the molar ratio of naphthalene sulfonate, acrylic acid, and acrylamide is 1:1:1), and transfer the mixture into a stirred reactor, continuously introduce high-purity nitrogen gas for 30 min to remove oxygen, and control the initial temperature of the system at 6℃. Simultaneously add 30% ammonium persulfate and 30% sodium bisulfite initiators, with the total initiator amounting to 6% of the total monomer mass, along with a chain transfer agent (mercaptopropionic acid, 0.1%). The addition time is 1.5–2 hours. After addition, the system is naturally heated to 60°C and maintained at this temperature for 4 hours. Finally, adjust the pH to 7–8 with NaOH. The general molecular formula is [(C3H3O2)]. x ·(C3H4NO) y ·(C 10 H6SO3M) z ] n (M is Na + (Isocational, x / y / z are variable molar ratios, n is the degree of polymerization), the polymer weight-average molecular weight is 20000 g / mol.
[0081] (2) Polyaspartic acid: The manufacturer is Hubei Rishengchang New Material Technology Co., Ltd., with a purity of 95%, industrial grade, and molecular formula (C4H7NO4). n , where n is the degree of polymerization and the molecular weight is 3000-5000.
[0082] Hardening modifier used ① This is a fine powder of refining slag from an LF furnace quenching process, containing amorphous C. 12 The A7 content is 35.6 wt%, and the β-C2S content is 27.4 wt%.
[0083] The density regulator used was 10 parts of polyethyleneimine (polyethyleneimine, CAS No. 9002-98-6, molecular formula H(NHCH2CH2)). n NH2, Aladdin reagent (product number E107078), molecular weight 1800), 50 parts sodium rosinate (CAS No.: 14351-66-7, molecular formula C 20 H 29NaO2, Aladdin reagent (product number S160978, molecular weight: 324.44), and 40 parts of modified α-alkenyl sulfonate (sodium α-alkenyl sulfonate and acrylamide were mixed at a molar ratio of 1:2, and an initiator (total monomer amount 0.1wt%) was added, and polymerization was carried out at 50℃ for 5h; then formaldehyde and secondary amine (diethylamine) (the molar ratio of the two to acrylamide was 0.5 and 0.75, respectively) were added, and a Mannich reaction was carried out for 3.5h to generate a modified product containing tertiary amine groups, which significantly improved its foaming salt resistance and foam stability).
[0084] Example 1
[0085] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 50 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 0.1 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ① Add 1 part of mud plasticizer in sequence and stir evenly to form fluidized solidified soil.
[0086] Example 2
[0087] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 50 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 0.1 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 5 parts of curing agent were added. ① Add 1 part of mud plasticizer in sequence and stir evenly to form fluidized solidified soil.
[0088] Example 3
[0089] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 50 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 0.1 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The resulting homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was transferred to a mixing tank, and then 15 parts of curing agent were added. ① Add 1 part of mud plasticizer in sequence and stir evenly to form fluidized solidified soil.
[0090] Example 4
[0091] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 80 parts of pre-treated waste soil and 50 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 0.1 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 8 parts of curing agent were added. ① Add 1 part of mud plasticizer in sequence and stir evenly to form fluidized solidified soil.
[0092] Example 5
[0093] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 95 parts of pre-treated waste soil and 50 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 0.1 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The resulting homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 12 parts of curing agent were added. ① Add 1 part of mud plasticizer in sequence and stir evenly to form fluidized solidified soil.
[0094] Example 6
[0095] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil B is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 60 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 0.1 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ① Add 1 part of mud plasticizer in sequence and stir evenly to form fluidized solidified soil.
[0096] Example 7
[0097] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil B is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 60 parts of water are fed into an overflow-type wet ball mill for mixing and grinding in appropriate proportions. During this process, 8 parts of an anti-organic matter regulating material are added. ① This forms solid particle size D 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ① Add 1 part of mud plasticizer in sequence and stir evenly to form fluidized solidified soil.
[0098] Example 8
[0099] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil B is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 60 parts of water are fed into an overflow-type wet ball mill for mixing and grinding in appropriate proportions. During this process, 8 parts of an anti-organic matter regulating material are added. ② To reduce the impact of organic matter in the slag on the mud performance, a homogeneous mud with uniform and controllable particle size and texture is formed. Next, the prepared homogeneous mud is placed in a mixing tank, and then 10 parts of solidifying agent are added. ① Add 1 part of mud plasticizer in sequence and stir evenly to form fluidized solidified soil.
[0100] Example 9
[0101] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil B is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 60 parts of water are fed into an overflow-type wet ball mill for mixing and grinding in appropriate proportions. During this process, 8 parts of an anti-organic matter regulating material are added. ③ To reduce the impact of organic matter in the slag on the mud performance, a homogeneous mud with uniform and controllable particle size and texture is formed. Next, the prepared homogeneous mud is placed in a mixing tank, and then 10 parts of solidifying agent are added. ① Add 1 part of mud plasticizer in sequence and stir evenly to form fluidized solidified soil.
[0102] Example 10
[0103] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil B is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 60 parts of water are fed into an overflow-type wet ball mill for mixing and grinding in appropriate proportions. During this process, 8 parts of an anti-organic matter regulating material are added. ④ To reduce the impact of organic matter in the slag on the mud performance, a homogeneous mud with uniform and controllable particle size and texture is formed. Next, the prepared homogeneous mud is placed in a mixing tank, and then 10 parts of solidifying agent are added. ① Add 1 part of mud plasticizer in sequence and stir evenly to form fluidized solidified soil.
[0104] Example 11
[0105] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil B is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 60 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 8 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ① 1.8 parts of mud plasticizer are added in sequence and stirred evenly to form fluidized solidified soil.
[0106] Example 12
[0107] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 50 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 0.1 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ① Add 1 part mud plasticizer and 3 parts hardening regulator in sequence, and stir evenly to form fluidized solidified soil.
[0108] Example 13
[0109] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 50 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 0.1 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The resulting homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was transferred to a mixing tank, and then 15 parts of curing agent were added. ① Add 1 part mud plasticizer and 1 part density regulator in sequence, and stir evenly to form fluidized solidified soil.
[0110] Compare with Example 1
[0111] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 50 parts of water are added to an overflow-type wet ball mill for mixing, stirring, and grinding to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ① Add and mix thoroughly to form a fluidized solidified soil filling material.
[0112] Compare with Example 2
[0113] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 50 parts of water are added to an overflow-type wet ball mill for mixing, stirring, and grinding to form solid particles of size D. 50 The resulting slurry was a homogeneous mud with a thickness of 200±10μm. Next, the prepared slurry was placed in a mixing tank, and then 10 parts of pure silicate cement were added as a curing agent. The mixture was stirred until homogeneous to form a fluidized, solidified soil filling material.
[0114] Compare with Example 3
[0115] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 50 parts of water are added to an overflow-type wet ball mill for mixing, stirring, and grinding to form solid particles of size D. 50 The homogeneous slurry has a thickness of 200±10μm. Next, the prepared homogeneous slurry is put into a mixing tank, and then 10 parts of a commonly used curing agent (composed of 50 parts of silicate cement, 35 parts of granulated blast furnace slag powder, and 15 parts of pulverized coal fly ash) are added and stirred evenly to form a fluidized solidified soil filling material.
[0116] Compare with Example 4
[0117] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 50 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 0.1 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ① One part of commercially available naphthalene-based high-efficiency water-reducing agent (CAS No. 36290-04-7, chemical composition is sodium β-naphthalenesulfonate formaldehyde condensate (sodium salt of sodium β-naphthalenesulfonate formaldehyde condensate), molecular formula is (C 10 H6CH2NaSO3) n The polymers (with a degree of polymerization n of 9-12 and an average molecular weight of approximately 2000-2400, and a water reduction rate of 20%-25% when used in concrete) are added sequentially and stirred evenly to form a fluidized solidified soil.
[0118] Compare with Example 5
[0119] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 50 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 0.1 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ① One part of commercially available polycarboxylate superplasticizer (pale yellow liquid, synthesized from methyl allyl polyoxyethylene ether (TPEP), with the general molecular formula CH2=C(CH3)CH3O(CH2CH2O)). n H (n is the degree of polymerization, molecular weight 30,000~40,000, solid content 20%, pH value 7.5, water reduction rate of 25%-35% when applied to concrete) are added sequentially and stirred evenly to form fluidized solidified soil.
[0120] Compare with Example 6
[0121] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil B is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 60 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 8 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ② 1.8 parts of mud plasticizer are added in sequence and stirred evenly to form fluidized solidified soil.
[0122] Compare with Example 7
[0123] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil B is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 60 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 8 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ③1.8 parts of mud plasticizer are added in sequence and stirred evenly to form fluidized solidified soil.
[0124] Compare with Example 8
[0125] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil B is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 60 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 8 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ④ 1.8 parts of mud plasticizer are added in sequence and stirred evenly to form fluidized solidified soil.
[0126] Compare with Example 9
[0127] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil B is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 60 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 8 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ⑤ 1.8 parts of mud plasticizer are added in sequence and stirred evenly to form fluidized solidified soil.
[0128] Compare with Example 10
[0129] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil B is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 60 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 0.1 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ① Add 1 part of commercially available naphthalene-based high-efficiency water-reducing agent in sequence and stir evenly to form fluidized solidified soil.
[0130] Compare with Example 11
[0131] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil B is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 60 parts of water are fed into an overflow-type wet ball mill for mixing and grinding. During this process, 0.1 parts of an anti-organic matter regulating material are added to form solid particles of size D. 50 The homogeneous slurry had a thickness of 200 ± 10 μm. Next, the prepared homogeneous slurry was placed in a mixing tank, and then 10 parts of curing agent were added. ① One part of commercially available polycarboxylate superplasticizer (pale yellow liquid, synthesized from methyl allyl polyoxyethylene ether (TPEP), with the general molecular formula CH2=C(CH3)CH3O(CH2CH2O)). n H (n is the degree of polymerization, molecular weight 30,000~40,000, solid content 20%, pH value 7.5, water reduction rate of 25%-35% when applied to concrete) are added sequentially and stirred evenly to form fluidized solidified soil.
[0132] Compare with Example 12
[0133] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 50 parts of water are mixed and ground in an overflow-type wet ball mill according to the appropriate ratio. During this process, 0.1 parts of an anti-organic matter control material are added to reduce the impact of organic matter in the waste soil on the slurry properties, forming a slurry with uniform and controllable particle size and texture. Third, the prepared homogenized slurry is placed in a mixing tank, and then 10 parts of a solidifying agent are added. ① Add 1 part mud plasticizer and 3 parts common NaOH coagulant in sequence, and stir evenly to form fluidized solidified soil.
[0134] Compare with Example 13
[0135] This example provides a controllable low-strength backfill material based on engineering waste soil. The preparation process is as follows: Engineering waste soil A is selected. First, it is pre-crushed to a size of less than 5mm using a crusher and then mixed and homogenized. Second, 90 parts of pre-treated waste soil and 50 parts of water are mixed and ground in an overflow-type wet ball mill according to the appropriate ratio. During this process, 0.1 parts of an anti-organic matter control material are added to reduce the impact of organic matter in the waste soil on the slurry properties, forming a slurry with uniform and controllable particle size and homogeneous texture. Third, the prepared homogeneous slurry is placed in a mixing tank, and then 15 parts of a solidifying agent are added. ①Add 1 part mud plasticizer and 3 parts commonly used 30wt% hydrogen peroxide foaming agent in sequence, and stir evenly to form fluidized solidified soil.
[0136] Performance tests were conducted on the fluidized solidified soil backfill material prepared in the above embodiments.
[0137] The basic physical properties of the two types of engineering waste soil used are shown in Table 1.
[0138] Table 1 Basic Physical Properties of Engineering Slag
[0139]
[0140] The main characteristics of the chemical composition and fineness of the high-alumina iron-phase cementitious material, spodumene smelting slag powder, converter steel slag powder, high-activity slag powder, and gypsum powder used in the experiment are as follows: (1) The high-alumina iron-phase cementitious material contains 18.2 wt% C4AF, 54.5 wt% calcium aluminate, and has a specific surface area of 374 m². 2 / kg; (2) The content of (SiO2+Al2O3) in the spodumene smelting slag powder is 79.3wt%, the content of amorphous glass phase is 42.6wt%, and D 50 The thickness is 7.4 μm; (3) The CaO content in the converter steel slag powder is 51.2 wt%, the CaO / SiO2 ratio is 2.6, (FeO+Fe2O3) is 19.4 wt%, and D 50 It has a diameter of 8.9 μm and a specific surface area of 532 m². 2 / kg; (4) The (CaO+MgO+Al2O) / (SiO2+Ti2O+MnO) ratio in the highly active slag powder is 1.67, the amorphous glass phase is 92.4wt%, the MgO content is 7.1wt%, the Fe2O3 content is 2.3wt%, and the D 50 It has a diameter of 9.6 μm and a specific surface area of 508 m². 2 / kg; (5) The CaO content in the circulating fluidized bed fly ash is 15.8wt%, f-CaO is 1.7wt%, D 50 The 80μm sieve residue is 8.2μm; (6) The gypsum powder is β-type phosphogypsum powder, with a β-CaSO4·1 / 2H2O content of 85.6wt% and an 80μm sieve residue of 3.4wt%.
[0141] During the performance testing of fluidized solidified soil backfill material, the curing method involves first curing the molded sample (covered with film) indoors at a temperature of 20±2℃ for 3 days. After demolding, the sample block is wrapped with plastic wrap and placed in a standard curing room (humidity ≥95wt% and temperature 20±2℃) for 28 days.
[0142] The fluidity test shall be performed in accordance with the test method for "fluidity of cement paste" in GB / T 8077-2023 "Test Method for Homogeneity of Concrete Admixtures" and the truncated cone mold.
[0143] The setting and hardening time test uses the depth of the Vicat probe penetrating the sample to characterize the degree of setting and hardening of the fluidized solidified soil. In this test, the setting and hardening time of the material is defined as 4 ± 1 mm from the bottom plate after penetrating the sample.
[0144] The wet apparent density test shall be performed in accordance with GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures".
[0145] The compressive strength test shall be performed in accordance with GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)".
[0146] The measured fluidity, setting and hardening time, wet apparent density and compressive strength results are shown in Table 2.
[0147] Table 2 Performance results of the prepared filling materials
[0148]
[0149] As can be seen from the results in Table 2, compared with conventional technologies, the present invention exhibits superior performance in terms of fluidity, setting and hardening time, apparent wet density, and early and late-stage properties of the fluidized solidified soil backfill material prepared using different types of engineering waste. The main features are as follows:
[0150] Compared with Examples 1, 2, and 3, under the same process without plasticizers and anti-organic matter control materials, the early and late strength of the filling material using the curing agent of the present invention is much higher than that of pure cement curing agent and commercially available curing agents. Moreover, the effect of promoting the setting and hardening time of the filling material is also better than that of commonly used pure cement curing agent and commercially available curing agents.
[0151] Compared to Examples 1, 2, and 3, under the same process, the apparent density and early and late strength of the filling material increased with the increase of the curing agent dosage of the present invention, while the fluidity and setting time decreased with the increase of the curing agent dosage. This indicates that increasing the curing agent dosage can promote the setting, hardening, density, and mechanical properties of the filling material. Although the increase of the curing agent dosage will cause a slight decrease in fluidity due to its own hydration, the impact is limited. The overall performance of the filling materials with 5-15 parts of the curing agent of the present invention is still within the optimal range. Furthermore, compared with Control Examples 2 and 3, the 28-day strength of the filling material with only 5% of the curing agent of the present invention is close to or even exceeds that of commercially available curing agents with 10% dosage, demonstrating the advantage of using the curing agent of the present invention to reduce the dosage, resulting in low carbon emissions and high efficiency.
[0152] Compared with Examples 1, 4, and 5, under the same process, the filling material with 8-12 parts of curing agent added to 80-95 parts of slag has less performance fluctuation and excellent comprehensive performance (flowability of 168-221 mm, setting and hardening time of 11.5-15.7, apparent density of 1594-1634, and 28-day strength of 1.23-1.86 MPa).
[0153] Compared with Control Example 1, the filler material prepared without plasticizer and anti-organic matter control material had poor flowability, which affected the density and strength of the filler material. However, under the same process conditions, the addition of the plasticizer and anti-organic matter control material of the present invention can significantly improve the flowability and workability of the filler material, and promote the density and strength of the material.
[0154] Compared with Example 6, under the same process, silty slag with high organic matter content has a great impact on the performance of backfill materials, especially the gel hardening time is greatly extended and the early and late strength is significantly reduced. Appropriate dosage of anti-organic matter regulating material can effectively solve the serious impact of humic acid in silty slag on the performance of backfill materials.
[0155] Examples 7, 8, 9, and 10 show that the anti-organic matter regulating material of the present invention can effectively solve the serious impact of humic acid in silty slag on the performance of backfill materials. The mixed polyol amine, zirconium acetate, and ultrafine metakaolin in the anti-organic matter regulating material have excellent synergistic effects, and the anti-organic matter effect is best when the three are combined.
[0156] Compared with Comparative Examples 6, 7, 8, and 9, Example 11 shows that the combination of high-alumina iron-phase cementitious material, spodumene smelting slag powder, converter steel slag powder, highly active slag powder, circulating fluidized bed fly ash, and gypsum in the curing agent of the present invention has excellent synergistic effects.
[0157] Compared with Comparative Examples 4 and 5, under the same process conditions for preparing fluidized solidified soil backfill material using engineering waste soil A, the fluidity of the backfill material using the plasticizer of the present invention is much higher than that of commercially available naphthalene-based high-efficiency water-reducing agents and commercially available polycarboxylate high-efficiency water-reducing agents. This promotes the comprehensive effect of improving the compactness (apparent density), shortening the setting and hardening time, and improving the strength of the backfill material. Furthermore, compared with Comparative Examples 10 and 11, under the same process conditions using engineering waste soil B, Example 6 also confirmed the above-mentioned consistent effects.
[0158] Compared with Control Example 12, Example 12 uses a commonly used NaOH coagulant to accelerate the hardening time of the filling material, but it has a significant negative impact on the material's fluidity and later strength growth. The hardening regulator of the present invention has the advantage of not only promoting the material's solidification and hardening, but also significantly improving the early and later strength development, and having a smaller impact on fluidity.
[0159] Compared with Control Example 13, the use of common foaming agents often leads to a significant decrease in material strength, or even no strength in the early stage, while adjusting the material to be lightweight. However, the density regulator of the present invention, when the density is controlled to be consistent, has a 28-day strength that is 2.6 times that of the control example, which is significantly effective.
[0160] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent changes, or alterations made to the above embodiments without departing from the technical essence of the present invention shall still fall within the scope of the present invention.
Claims
1. A controllable low-strength backfill material based on engineering waste soil, characterized in that: The raw materials comprise the following parts by weight: 80-95 parts of engineering waste soil, 5-15 parts of waste soil solidification agent, 0.1-10 parts of anti-organic matter regulating material, 0.1-2 parts of mud plasticizer, 0-5 parts of hardening regulator, and 0-2 parts of density regulator; the raw materials meet the following conditions: (i) The anti-organic matter regulation material comprises at least two of the following: mixed polyol amines, zirconium acetate, and ultrafine metakaolin; (ii) The slurry plasticizer comprises at least two of the following: acrylic acid-acrylamide modified naphthalene sulfonate copolymer, polyaspartic acid, layered silica, and cyclic sodium polyphosphate; (iii) The slag solidification agent comprises the following components: high-alumina ferrophase cementitious material, spodumene smelting slag powder, converter steel slag powder, high-activity slag powder, circulating fluidized bed fly ash and gypsum powder; wherein, the components have the following characteristics: (1) High-alumina ferrophase cementitious material: C4AF > 15wt%; calcium aluminate content > 50wt%; specific surface area 350-400m² 2 / kg; (2) Lithium spodumene smelting slag powder: SiO2 content + Al2O3 content > 70wt%, amorphous glass phase > 40wt%, D 50 <10μm; (3) Converter steel slag powder: CaO content between 50wt% and 60wt%, CaO to SiO2 mass ratio >2.5, (FeO+Fe2O3) <20wt%, f-CaO content <2wt%, D 50 <10μm, specific surface area >500m² 2 / kg; (4) High-activity slag powder: the ratio of the sum of the masses of CaO, MgO, and Al2O3 to the sum of the masses of SiO2, Ti2O, and MnO is >1.6, the amorphous glass phase is >90wt%, the MgO content is <8wt%, the Fe2O3 content is <2.5wt%, and the D 50 <10μm, specific surface area >500m² 2 / kg; (5) Circulating fluidized bed fly ash: CaO content between 10-20wt%, D 50 <10μm; (6) Gypsum powder: The components include β-type desulfurized gypsum powder or β-type phosphogypsum powder, β-CaSO4·1 / 2H2O content ≥80wt%, 80μm sieve residue ≤10wt%.
2. The controllable low-strength backfill material based on engineering waste soil according to claim 1, characterized in that: The anti-organic matter regulating material includes a mixed polyol amine, zirconium acetate and ultrafine metakaolin, wherein the mass ratio of the mixed polyol amine, zirconium acetate and ultrafine metakaolin is 1:3~5:10~20.
3. A controllable low-strength backfill material based on engineering waste soil according to claim 1 or 2, characterized in that: The mixed polyamine comprises 15-25 parts N-methyldiethanolamine, 20-40 parts triethanolamine, 15-25 parts diisopropanolamine, and 20-40 parts triisopropanol.
4. The controllable low-strength backfill material based on engineering waste soil according to claim 1, characterized in that: The mud plasticizer contains an acrylic acid / acrylamide modified naphthalene sulfonate copolymer.
5. A controllable low-strength backfill material based on engineering waste soil according to claim 1, characterized in that: The mass ratio of the curing agent to the pretreated waste soil is 8~12:80~95.
6. A controllable low-strength backfill material based on engineering waste soil according to claim 5, characterized in that: The slag solidification agent is composed of the following components by weight: 5-15 parts of high-alumina iron phase cementitious material, 5-15 parts of spodumene smelting slag powder, 20-40 parts of converter steel slag powder, 20-40 parts of high-activity slag powder, 10-30 parts of circulating fluidized bed fly ash, and 5-15 parts of gypsum powder.
7. A controllable low-strength backfill material based on engineering waste soil according to claim 1, characterized in that: The hardening regulator includes LF furnace refining slag powder quenched by air, wherein the LF furnace refining slag powder contains amorphous C. 12 A7 mineral phase content > 30wt%, β-C2S content > 20wt%; and / or, the density regulator comprises a combination of polyethyleneimine, rosin soap, and modified α-alkenyl sulfonate, wherein the mass ratio of polyethyleneimine, rosin soap, and modified α-alkenyl sulfonate is 1~2:4~6:3~5.
8. The method for preparing the controllable low-strength filling material according to any one of claims 1 to 7, characterized in that: Includes the following steps: The waste soil from the project is mixed with water and then stirred and ball-milled. During the stirring and ball-milling process, an anti-organic matter regulating material is added to form a slurry. A waste soil solidifier and a slurry plasticizer are then added to the slurry to obtain the final product.
9. The method of using the controllable low-strength filling material according to any one of claims 1 to 7, characterized in that: Includes the following steps: Before pouring, a hardening regulator and / or density regulator are added to the controllable low-strength filling material, and the mixture is then poured.
10. The application of the controllable low-strength filling material according to any one of claims 1 to 7 in the construction of infrastructure, transportation engineering or mining engineering.